THE ROLE OF BIG DATA IN IMPROVING MARKET MICROSTRUCTURE EFFICIENCY: A LITERATURE REVIEW - Fairuz Rifqi Abdurahman; Maya Sari (Jurnal Ekonomi, 2023)
The development of information and communication technology has resulted in an unprecedented explosion of data, known as Big Data. This phenomenon has influenced various aspects of the economy, including Market Microstructure, which is a highly detailed study of the behavior and structure of financial markets. Big Data has enabled market researchers and practitioners to improve the efficiency of Market Microstructure in an unprecedented way. This study utilizes the literature review method to investigate the role of Big Data in improving Market Microstructure efficiency. The results of the literature review show that Big Data has the potential to change the Market Microstructure landscape in several key ways. First, Big Data enables more sophisticated and real-time market monitoring, allowing for faster and more accurate decision-making. Second, Big Data can be used to analyze larger and more complex market data, which can reveal patterns and trends that were previously difficult to discover. Thirdly, Big Data enables the development of better predictive models to forecast price movements and market liquidity. In addition, the literature review also revealed challenges and issues associated with the use of Big Data in Market Microstructure, including data privacy and security concerns, as well as difficulties in managing and analyzing massive and diverse data. Therefore, the use of Big Data in Market Microstructure requires careful attention to ethical and regulatory aspects. In order to improve the efficiency of the Market Microstructure, Big Data has opened up exciting new opportunities, but also presents challenges that need to be addressed. With the right approach, Big Data can provide valuable insights and improve our understanding of financial market behavior, which in turn can improve market efficiency and benefit stakeholders in the financial markets.